2017
DOI: 10.1093/pm/pnx153
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain After Traumatic Brain Injury: Pathophysiology and Pain Mechanisms

Abstract: This review presents evidence that pain is common after traumatic brain injury. However, while there are many potential mechanisms explaining this problem such as neuroinflammation, excitotoxicity, and axonal degeneration, we have no clear understanding of which of them contribute in individual patients. The authors highlight the priorities for research that will expand our knowledge and that may lead to the rational design of therapies that both reduce pain and provide optimal overall outcomes after traumatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 167 publications
1
63
0
6
Order By: Relevance
“…The estimated global yearly incidence of traumatic brain injury (TBI) is 106/100,000 capita, whereas it is around 600/100,000 capita in the case of mild TBI [57, 58]. Some 13 million people is estimated to live with disabilities related to TBI in Europe and the USA [59].…”
Section: Chronic Central Npmentioning
confidence: 99%
“…The estimated global yearly incidence of traumatic brain injury (TBI) is 106/100,000 capita, whereas it is around 600/100,000 capita in the case of mild TBI [57, 58]. Some 13 million people is estimated to live with disabilities related to TBI in Europe and the USA [59].…”
Section: Chronic Central Npmentioning
confidence: 99%
“…In the United States, more than 2.5 million injuries occur per year (Centers for Disease Control and Prevention, 2015), with the majority of these cases being mild in nature 3 . While many symptoms of mild TBI dissipate rapidly after injury, these patients frequently experience unusually high rates of acute and chronic pain 4,5 . Headache commonly occurs after TBI, although pain can be widespread and may include the back and extremities 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Structural and functional alterations affecting pain processing and the neuroendocrine modulation of pain may lead to an increased risk of chronic pain after TBI. 16,21 If risk of chronic pain increases with greater severity of injury to the brain, this would explain why our study found no associations of mTBI with future back pain, but did find associations with moderate to severe TBI. However, there are many other explanations other than a causal link, including those described above, which may partially or completely explain the moderate to severe TBIback pain association.…”
Section: Discussionmentioning
confidence: 59%
“…22,35 Various theoretical mechanisms may explain an increased risk of pain after TBI, including alterations in descending (inhibitory) regulation of pain, ascending pain pathways, dopamine signaling, neuroinflammation, neurodegenerative processes, diffuse axonal injury, synaptic dysfunction, and others. 16,21 Alternatively, the link between pain and TBI may be explained by shared risk factors for both conditions, such as major physical traumas causing both brain injury and musculoskeletal injury at the same time. To our knowledge, no prior longitudinal studies including a comparison group of those without TBI have been conducted to examine whether clinically defined TBI is a risk factor for specific chronic pain syndromes other than headache.…”
mentioning
confidence: 99%